EVALUASI STABILITAS FISIK FORMULA SEDIAAN SUSPENSI EKSTRAK TERIPANG NANAS (Thelenota ananas) DENGAN VARIASI KONSENTRASI NA CMC DAN SORBITOL - Azizah Ahsaninnisa; Ahmad Fauzi (Jurnal Insan Farmasi Indonesia, 2025)
Suspense preparation formulation of pineapple sea cucumber extract as an active substance of protein functions in improving immunity. Solubility is the basis for making oral suspension preparations. The main challenge in suspension formulation is physical stability. Problems that often occur include inadequate viscosity, sedimentation and redispersibility. This study aims to determine the physical stability of pineapple sea cucumber extract suspense preparations with varying concentrations of Na CMC and Sorbitol with physical stability parameters including organoleptical tests, pH, viscosity, sedimentation volume, and redispersion. The test results of the suspension preparation have an influence on physical stability. Meanwhile, the variation of Na CMC and sorbitol has no effect on the pH of the preparation. The seven formulas evaluated for physical stability meet the requirements for good suspense preparations from organoleptics, pH, viscosity, sedimentation volume, and redispersibility.